Employee Perceptions of Sustainability Programs: Motivation or Green Fatigue - Rury Nur Utomo; Achmad Ghazali (International Journal Labs, 2026)
The increasing adoption of Environmental, Social, and Governance (ESG) practices has encouraged organizations to implement sustainability programs as part of their strategic and operational activities. Although sustainability initiatives are expected to enhance employee engagement and organizational commitment, excessive sustainability demands may potentially create psychological pressure and green fatigue among employees. This study aimed to examine whether employees perceive workplace sustainability programs primarily as a source of motivation or as a contributor to green fatigue. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 202 employees working in organizations implementing sustainability or ESG-related initiatives in Indonesia. The collected data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS to evaluate the relationships between Sustainability Program Perception, Employee Motivation, and Green Fatigue. The results showed that sustainability program perception had a significant positive effect on employee motivation (? = 0.699, p < 0.001), indicating that sustainability initiatives can strengthen employee engagement, organizational pride, and meaningful work experiences. However, sustainability program perception did not significantly influence green fatigue (? = -0.018, p = 0.889), and employee motivation also showed no significant effect on green fatigue (? = -0.156, p = 0.199). These findings indicate that sustainability programs function more as motivational drivers rather than sources of employee exhaustion. The study concludes that organizations should integrate sustainability initiatives with effective communication, employee participation, and recognition systems to maximize motivational benefits while maintaining employee well-being.